PSRC1 May Affect Coronary Artery Disease Risk by Altering CELSR2, PSRC1, and SORT1 Gene Expression and Circulating Granulin and Apolipoprotein B Protein Levels - Chai, Tianci; Wang, Zhisheng; Yang, Xiaojie; Qiu, Zhihuang; Chen, Liangwan (Frontiers in Cardiovascular Medicine, 2022)
Objective The aim of the study was to identify additional factors that contributed to coronary artery disease (CAD). Methods We conducted integrative analysis on publicly available data from genome-wide association studies and quantitative trait locus studies by employing Mendelian randomization methods to examine the associations of gene expression in liver cells and circulating protein levels with LDL-C and CAD. Results We found that the mRNA expression levels of CELSR2, PSRC1, SORT1, SYPL2, RHD, RHCE, ANGPTL3, ATXN7L2, DNAH11, FADS3, ST3GAL4, NYNRIN, CETP, EFCAB13, and SPTLC3 were significantly associated with LDL-C. The expression levels of SORT1, PSRC1, and CELSR2 in liver cells were significantly associated with CAD. Higher expression levels of SORT1, PSRC1, and CELSR2 in the liver were significantly associated with lower circulating LDL-C levels and CAD risk. PSRC1 variants were strongly associated with SORT1, PSRC1, and CELSR2 gene expression in liver cells. Higher circulating granulin and apolipoprotein B levels, which were strongly affected by PSRC1 variants, were significantly associated with higher LDL-C levels and CAD risk, with odds ratios of 1.15 (1.10–1.19) and 1.45 (1.21–1.74), respectively. Conclusion This study showed that regulatory SNPs in PSRC1 may affect CAD risk by altering CELSR2, PSRC1, and SORT1 gene expression in liver cells and circulating granulins and apolipoprotein B proteins.